2023
DOI: 10.3310/nihropenres.13427.2
|View full text |Cite
|
Sign up to set email alerts
|

Covariates of success in quitting smoking: a systematic review of studies from 2008 to 2021 conducted to inform the statistical analyses of quitting outcomes of a hospital-based tobacco dependence treatment service in the United Kingdom

Emma S. Hock,
Matthew Franklin,
Susan Baxter
et al.

Abstract: Background Smoking cessation interventions are being introduced into routine secondary care in the United Kingdom (UK), but there are person and setting-related factors that could moderate their success in quitting smoking. This review was conducted as part of an evaluation of the QUIT hospital-based tobacco dependence treatment service (https://sybics-quit.co.uk). The aim of the review was to identify a comprehensive set of variables associated with quitting success among tobacco smokers contacting secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Our statistical analysis plan development was supported by a literature review to identify factors that might be associated with quitting outcomes. 30 Further details of population eligibility criteria and the covariates of interest were developed in the interim QUIT service evaluation report. 25 The evaluation team refined the analysis plan through regular discussions with the QUIT service team, including the programme director and manager, through the stages of evaluation planning, data collection, and data curation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our statistical analysis plan development was supported by a literature review to identify factors that might be associated with quitting outcomes. 30 Further details of population eligibility criteria and the covariates of interest were developed in the interim QUIT service evaluation report. 25 The evaluation team refined the analysis plan through regular discussions with the QUIT service team, including the programme director and manager, through the stages of evaluation planning, data collection, and data curation.…”
Section: Discussionmentioning
confidence: 99%
“…25 First, we conducted a literature review that was designed to identify factors that could be related to quitting outcomes. 30 Second, we cross-referenced the literature review’s suggested variables with the available CSSS data fields, which we grouped into four categories: “demographic and socio-economic factors”, “tobacco smoking factors”, “intervention characteristics” and “health and healthcare setting”. These categories are described below, with further details in the Supplementary Information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation